Endoplasmic Reticulum Stress-Activated Transcription Factor ATF6α Requires the Disulfide Isomerase PDIA5 To Modulate Chemoresistance - Higa, Arisa (American Society for Microbiology, 2014)
ATF6α, a membrane-anchored transcription factor from the endoplasmic reticulum (ER) that modulates the cellular response to stress as an effector of the unfolded-protein response (UPR), is a key player in the development of tumors of different origin. ATF6α activation has been linked to oncogenic transformation and tumor maintenance; however, the mechanism(s) underlying this phenomenon remains elusive. Here, using a phenotypic small interfering RNA (siRNA) screening, we identified a novel role for ATF6α in chemoresistance and defined the protein disulfide isomerase A5 (PDIA5) as necessary for ATF6α activation upon ER stress. PDIA5 contributed to disulfide bond rearrangement in ATF6α under stress conditions, thereby leading to ATF6α export from the ER and activation of its target genes. Further analysis of the mechanism demonstrated that PDIA5 promotes ATF6α packaging into coat protein complex II (COPII) vesicles and that the PDIA5/ATF6α activation loop is essential to confer chemoresistance on cancer cells. Genetic and pharmacological inhibition of the PDIA5/ATF6α axis restored sensitivity to the drug treatment. This work defines the mechanisms underlying the role of ATF6α activation in carcinogenesis and chemoresistance; furthermore, it identifies PDIA5 as a key regulator ATF6α-mediated cellular functions in cancer.